A trifunctional polyethylene oxide buffer layer for stable and efficient all-inorganic CsPbBr3 perovskite solar cells. Issue 13 (7th March 2023) - Tan, Jin; Dou, Jie; Duan, Jialong; Zhao, Yuanyuan; He, Benlin; Tang, Qunwei
Abstract : The trifunctional PEO buffer layer improved the photovoltaic performances of all-inorganic CsPbBr3 perovskite solar cells. Abstract : Carbon-based all-inorganic perovskite solar cells have attracted growing interest owing to their simple fabrication process, low cost, and high stability in air. On account of the large interfacial energy barriers and polycrystalline features of perovskite films, the carrier interface recombination and inherent defects in the perovskite layer are still great challenges in further increasing the power conversion efficiency and stability of carbon-based PSCs. We present here a trifunctional polyethylene oxide buffer layer at the perovskite/carbon interface to promote the PCE and stability of carbon-based all-inorganic CsPbBr3 PSCs: (i) the PEO layer increases the crystallinity of inorganic CsPbBr3 grains for low defect state density; (ii) the oxygenic groups in PEO chains passivate the defects on the perovskite surface; and (iii) the long hydrophobic alkyl chains improve the stability in moisture. The best encapsulated PSC achieves a PCE of 8.84% and maintains 84.8% of its initial efficiency in air with 80% RH over 30 days.